SPORTS MAJOR EVENT ORGANIZING FOR ECONOMIC RECOVERY OF BALI - Donny Fahrochi (Indonesia Sport Journal, 2022)
Covid19 pandemic has paralyze Bali completely. This paper offer an idea to organize major sporting event to restore it. By organize a large-scale sports event, will beneficial in many ways and accelerate Bali restoration. Economic side, branding, and legacy will be discussed.Keyword: Sport Event, Organizing, Recovery, Bali Tourism